Modelling and optimization of industrial manufacturing processes subject to no-wait constraints - Macchiaroli, R.; Mole, S.; Riemma, S. (International journal of production research, 1999)
This paper deals with scheduling of no-wait manufacturing processes. The main features of these systems are analysed and an industrial application is described in detail. No standard solution procedure has been devised in the literature for this difficult scheduling problem. We exploit a heuristic decomposition approach which allows the reduction of the searchable solutions space and makes use of sequencing and timetabling modules. The timetabling can be performed by a polynomial time algorithm. To make the sequencing decision we propose several heuristic rules, a decomposition approach making use of fuzzy logic and an algorithm based on tabu search. The extensive computational results reported show the clear superiority of the tabu search approach.